2019
DOI: 10.1002/dev.21844
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to tobacco and marijuana and child autonomic regulation and reactivity: An analysis of indirect pathways via maternal psychopathology and parenting

Abstract: We examined a conceptual model for the associations of prenatal exposure to tobacco (PTE) and marijuana with child reactivity/regulation at 16 months of age. We hypothesized that PTE would be associated with autonomic reactivity and regulation that these associations would be indirect via maternal anger/hostility, depression/stress, or harsh parenting assessed at 2 months and that these effects would be most pronounced among children exposed to both tobacco and marijuana (PTME). Participants were 247 dyads (81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
(92 reference statements)
1
10
1
Order By: Relevance
“…Tobacco is sometimes mixed not only with alcohol but also with narcotics; in particular the effect of prenatal combining tobacco with marijuana was studied. The study indicated an indirect association between this combination and autonomic functioning during the second year of life [ 60 ]. Similarly, a connection between prenatal cannabis exposure (mostly combined with tobacco) and cortical thickness was suggested [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco is sometimes mixed not only with alcohol but also with narcotics; in particular the effect of prenatal combining tobacco with marijuana was studied. The study indicated an indirect association between this combination and autonomic functioning during the second year of life [ 60 ]. Similarly, a connection between prenatal cannabis exposure (mostly combined with tobacco) and cortical thickness was suggested [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, neither cool nor hot inhibitory control emerged as a mechanism accounting for the link between early tobacco smoke exposure and internalizing problems. Thus, future research is warranted to test alternative explanatory mechanisms, such as emotion regulation strategies, maternal psychopathology, and parenting (Margolis et al, 2016; Schuetze et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among plausible psychological mechanisms, impaired self-regulation, especially inhibitory control, merits special attention (Clark, Massey, Wiebe, Espy, & Wakschlag, 2019; Wiebe et al, 2015). This proposition is based on numerous studies showing the implications of inhibitory control for psychopathology (Schoemaker, Mulder, Deković, & Matthys, 2013) and on accumulating evidence indicating that brain regions (e.g., prefrontal lobe) and neural systems (e.g., dopaminergic, serotonergic, and noradrenergic systems) variously implicated in self-regulatory activities are likely to be disrupted by early exposure to tobacco smoke (Holz et al, 2014; Lotfipour et al, 2009; Marroun et al, 2014; Schuetze, Zhao, Eiden, Shisler, & Huestis, 2019).…”
Section: Early Tobacco Smoke Exposure: Conceptualization and Developm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental risk factors account for significant variance in developmental outcomes among infants exposed to opioids prenatally (Konijnenberg & Melinder, 2011; Messinger et al., 2004). Parenting behaviors such as parental sensitivity and harshness may moderate or mediate the effects of prenatal substance exposure on developmental outcomes (Eiden et al., 2014; Flykt et al., 2021; Schuetze et al., 2019; Veira et al., 2014). Opioid‐exposed infants often exhibit autonomic dysregulation and are difficult to soothe (Kocherlakota, 2014).…”
Section: Introductionmentioning
confidence: 99%